Effects of family and neighborhood vulnerability on dual language learner and monolingual children’s preschool outcomes - Frechette, Liz; Castle, Sherri; Jeon, Shinyoung; Horm, Diane; Martinez, Irving; Vega Ruvalcaba, Denise; Schaefer, Shawn (Frontiers in Education, 2023)
Preschoolers from low-income families are often raised in neighborhood and home environments with elevated risks that impact their development (Jeon et al., 2014;Morrissey & Vinopal, 2018). More specifically, research has documented that home and neighborhood contexts of children from low-income families are associated with lower cognitive (Raver et al., 2013) and social-emotional skills (Bassett et al., 2012) than their higher-income peers. Over a third of young children growing up in poverty are dual language learners (DLLs) and speak Spanish in the home (Park et al., 2017). Although speaking two languages may be a protective factor for young DLLs growing up in poverty (Grote et al., 2021;Hanno & Surrain, 2019;Hartanto et al., 2019;Kim et al., 2018;López & Foster, 2021), little research has examined how contextual effects differ between DLL and monolingual children. The current study examines how DLL status may act as a buffer by moderating the negative associations between collective neighborhood vulnerability, individual family risk, and children's executive function (EF) and social-emotional skills.This study is rooted in the bioecological model (Bronfenbrenner & Morris, 2007), which suggests that children's development is shaped by multiple, nested contexts within their environment. The environment includes the neighborhood, classroom, and family contexts that interact with one another and influence children's development. For example, the various risks in a child's community (e.g., extreme poverty) or home (e.g., having a single parent) may influence the access to learning experiences a child has in their neighborhood or home.